Hubungan Komunikasi Interpersonal Perawat Dengan Kepatuhan Pasien Menjalankan Pengobatan Tuberkulosis di UPTD Puskesmas Kali Baru Bekasi - Arhani, Safinatunnajah; Pelawi, Arabta M Peraten; Lisna Agustina (Rena Cipta Mandiri, 2024)
Background: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis, or acid-fast bacilli (AFB), which can survive in low-oxygen environments. Factors influencing TB patient adherence include motivation, knowledge, attitude, and family support. Research Objective: To determine the relationship between nurse-patient interpersonal communication and patient adherence to TB treatment at UPTD Puskesmas Kalibaru, Bekasi. Research Method: This study used a quantitative method with an observational analytic design and a cross-sectional approach, involving 30 patients. The sampling technique used was total sampling. Results: The Chi-Square test yielded a p-value of 0.000 < α (0.05), indicating that H0 is rejected.Conclusion: There is a significant relationship between nurse-patient interpersonal communication and patient adherence to TB treatment at UPTD Puskesmas Kalibaru, Bekasi.